Ergonomic Risk Factors and Musculoskeletal Disorders (MSDs) Discomfort among Retail Workers in Batu Pahat - Suherman, Nuriyana; Ruslan, Rumaizah; Abdul Hamid, Norhadilah (Research in Management of Technology and Business, 2025)
Retail workers are routinely exposed to a range of occupational hazards, with ergonomic risk factors being a principal concern due to their potential to contribute to the development of musculoskeletal disorders (MSDs). Manual material handling including repetitive lifting, carrying, and moving of merchandise such as boxes and packages is a particularly prevalent risk within this sector. This study aims to systematically identify the key ergonomic risk factors encountered by retail workers in the execution of their daily tasks. Additionally, it seeks to evaluate the prevalence and severity of MSDs among these workers, with particular attention to the experiences of cashiers, and to elucidate the relationship between ergonomic exposures and reported musculoskeletal symptoms. A quantitative research approach was employed by distributing surveys to employees across several selected retail stores in Batu Pahat, Johor. The research population included a diverse range of job roles within the retail industry, ensuring a comprehensive representation of the workforce. Data collection focused on capturing ergonomic risk factors and self-reported musculoskeletal symptoms. Analysis of the collected data revealed that a significant proportion of retail workers experience musculoskeletal symptoms attributable to their work activities. Among cashiers, the prevalence of MSDs was predominantly at a moderate level, with the right shoulder, lower back, and right wrist reported as the most common sites of discomfort. Statistical analysis demonstrated a significant association between ergonomic risk factors and the incidence of MSDs. The findings underscore the importance of addressing ergonomic hazards in the retail sector, particularly those related to manual material handling and repetitive tasks. The observed relationship between ergonomic exposures and MSDs highlights the need for targeted prevention strategies. Future research and intervention programs should focus on mitigating these identified risk factors to promote occupational safety and health among retail workers.